2018
DOI: 10.1016/j.pjnns.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Immune-cell BDNF expression in treatment-naïve relapsing-remitting multiple sclerosis patients and following one year of immunomodulation therapy

Abstract: Although neurons are the main source of neurotrophins in the healthy brain, neurotrophins can also be expressed in the immune system. We have previously shown that in relapsing-remitting multiple sclerosis (RRMS) lower immune-cell neurotrophin levels are associated with brain atrophy and cognitive impairment. The aim of the present study was to assess if immune-cell neurotrophin expression is impaired in MS as compared with the healthy controls, and to describe if these levels change in treatment-naïve RRMS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…Again, for BDNF-AS none of patients' subgroups showed significance even subgroup of females ˂30 years old (3-fold change). This is well in line with Lindquist and Kalinowska-Łyszczarz works who found no quantitative change in BDNF protein in freshly isolated peripheral blood mononuclear cells (PBMCs) of MS patients, 27,28 and in contrast to those exhibiting significant changes. 19,22 One of the most straightforward explanations for this might be different sample sizes and heterogeneity of MS that, in part, contributes to these results.…”
Section: Discussionsupporting
confidence: 89%
“…Again, for BDNF-AS none of patients' subgroups showed significance even subgroup of females ˂30 years old (3-fold change). This is well in line with Lindquist and Kalinowska-Łyszczarz works who found no quantitative change in BDNF protein in freshly isolated peripheral blood mononuclear cells (PBMCs) of MS patients, 27,28 and in contrast to those exhibiting significant changes. 19,22 One of the most straightforward explanations for this might be different sample sizes and heterogeneity of MS that, in part, contributes to these results.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to our results, many studies found that BDNF levels in MS patients were significantly lower than those in the healthy control group [16][17][18]. The low BDNF secretion from immune cells of MS patients may be related to reduced neuroprotection [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, BDNF has neuroprotective effects through regulating the downstream transcription factor cAMP-response element binding protein (CREB) (De Santi et al, 2009). Clinical observation found low levels of BDNF expression in MS patients (Kalinowska-Łyszczarz et al, 2018). Experimental studies also found decreased expression of BDNF in the brain and spinal cord in mice with experimental autoimmune encephalomyelitis (EAE), an animal model of MS (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%